Peran Customer Experience Dalam Meningkatkan Kepuasan Pelanggan Pada Warkop Hendri Jaya Kuphi Di Ujung Fatihah Kabupaten Nagan Raya - Fatma Amelia; Muhammad Rahmat Hidayat (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study analyzes the role of Customer Experience (CX) strategies in improving Customer Satisfaction at Warkop Hendri Jaya Kuphi in Nagan Raya. Using a qualitative case study and Strategic Management Analysis (SWOT), data was obtained through in-depth interviews with the business owner. The results indicate that Relational Experience, the personal intimacy between staff and customers, is the most dominant CX factor that creates emotional loyalty and Customer Satisfaction. Warkop is positioned in an Aggressive Strategy (SO), leveraging this CX to capture market opportunities. It is recommended that Warkop Hendri Jaya Kuphi implement a local Blue Ocean Strategy by strengthening its unique CX and immediately preparing structured financial reports. CX has proven to be Warkop's primary competitive advantage in facing competition from MSMEs at the district level.